STRATEGI KOMUNIKASI PEMASARAN LIVE STREAMING AKUN TIKTOK @WHITEDIARY.ID - Riza Khirey Tri Pratiwi; Nur Maghfira Aesthetika (LPPM Stikosa - AWS, 2024)
This research aims to evaluate the effectiveness of the marketing communication strategy of the live streaming feature on the TikTok social media platform, focusing on the @WhiteDiary.id account. The methods used include observation and interviews with account owners and employees who work in the field of streamers in live streaming. The results showed that @WhiteDiary.id successfully utilized live streaming as an effective tool. Setting a regular and consistent live streaming schedule, personalized and friendly live interaction, as well as delivering detailed product information, has proven effective in increasing audience engagement and brand awareness. Analyzing the data from the live streams allowed for precise strategy adjustments, thus reaching a wider audience. This strategy helped @WhiteDiary.id achieve marketing goals in an innovative and relevant way, demonstrating that live streaming is a powerful digital marketing tool.